2022
DOI: 10.3389/fncel.2022.863426
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3-Dependent Pyroptosis: A Candidate Therapeutic Target for Depression

Abstract: Depression, a major public health problem, imposes a significant economic burden on society. Recent studies have gradually unveiled the important role of neuroinflammation in the pathogenesis of depression. Pyroptosis, a programmed cell death mediated by Gasdermins (GSDMs), is also considered to be an inflammatory cell death with links to inflammation. Pyroptosis has emerged as an important pathological mechanism in several neurological diseases and has been found to be involved in several neuroinflammatory-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Additionally, caspase-1 promotes the secretion of interleukins, leading to an inflammatory response. [48][49][50][51][52][53] The nonclassical pathway of pyroptosis is mediated primarily by caspase-4, 5, and 11. Activation of these caspases occurs upon stimulation of cells with bacterial LPS, whereby they bind directly to LPS and subsequently become activated.…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, caspase-1 promotes the secretion of interleukins, leading to an inflammatory response. [48][49][50][51][52][53] The nonclassical pathway of pyroptosis is mediated primarily by caspase-4, 5, and 11. Activation of these caspases occurs upon stimulation of cells with bacterial LPS, whereby they bind directly to LPS and subsequently become activated.…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
“…Additionally, caspase‐1 promotes the secretion of interleukins, leading to an inflammatory response. [ 48–53 ]…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
“…The NLRP3 inflammasome and subsequent pyroptosis have emerged as potential therapeutic targets for the treatment of depression . Several agents have shown promise in modulating the NLRP3 inflammasome and exerting antidepressant effects.…”
Section: Inhibition Of Inflammation and Nlrp3 For Treating Post-sci M...mentioning
confidence: 99%
“…The NLRP3 inflammasome and subsequent pyroptosis have emerged as potential therapeutic targets for the treatment of depression. 163 Several agents have shown promise in modulating the NLRP3 inflammasome and exerting antidepressant effects. For example, a Food and Drug Administration (FDA)-approved antidepressant, fluoxetine, was found to bind NLRP3 in silico and inhibit the NLRP3-ASC complex in vitro and in vivo.…”
Section: ■ Inhibition Of Inflammation and Nlrp3 For Treating Post-sci...mentioning
confidence: 99%
“…In recent years, an increasing number of scholars have found that neuroinflammation is an important pathological factor triggering central neurological disorders such as depression, and inhibiting central neuroinflammation is a key way to effectively alleviate the onset and progression of depression (12)(13)(14)(15)(16). It was found that upregulation of pro-inflammatory cytokines (IL-6 and TNF-α) was seen in the hippocampus and cortex of Lipopolysaccharide (LSP)-induced depressed mice (17).…”
Section: Cyclo-oxygen-ase-2 Roles In the Pathogenesis Of Depression N...mentioning
confidence: 99%